Vacuum-assisted blade coating method for preparing perovskite thin-film solar cell

Through vacuum-assisted scraping method, combined with the auxiliary technology of vacuum pump and thermal resistance wire, the problem of poor uniformity of large-area perovskite solar cell thin films is solved, and efficient perovskite film preparation and photoelectric conversion efficiency are achieved.

CN119816076APending Publication Date: 2025-04-11DATANG HAINAN WENCHANG NEW ENERGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411671465.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The photoelectric conversion efficiency of large-area perovskite solar cells is rapidly attenuated, mainly due to the difficulty in ensuring the uniformity of the film, resulting in different film quality and thickness in local areas.

Method used

Perovskite films are prepared by vacuum-assisted scraping method, and the suction force and heating of the electric heat-resisted wire are provided through a vacuum pump to improve the uniformity and crystallinity of the film.

Benefits of technology

The uniform preparation of large-area perovskite films is achieved, the mirror crystallization effect of the film is improved, and the photoelectric conversion efficiency of perovskite thin-film solar cells is enhanced, up to 16.83%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816076A_ABST
    Figure CN119816076A_ABST
Patent Text Reader

Abstract

The invention provides a vacuum-assisted blade coating method for preparing a perovskite thin-film solar cell, and the preparation method of a perovskite thin-film layer specifically comprises the following steps: fixing a substrate material on a table board of blade coating equipment, dropping a perovskite precursor solution in a micron-order gap between the substrate material and a scraper to form a liquid curtain, starting the blade coating equipment, and carrying out the vacuum-assisted blade coating method to prepare the perovskite thin-film solar cell. And performing blade coating on the perovskite thin film through a scraper, opening a vacuum pump, connecting the vacuum pump with a vacuum knife, discharging the solvent in the perovskite precursor solution through the vacuum knife by combining the temperature of the electric heating resistance wire, and after the blade coating process is completed, placing the substrate coated with the perovskite thin film on a heating table for annealing, thereby obtaining the perovskite thin film layer. According to the method, an air knife in an original blade coating method is replaced, a vacuum knife for vacuum air exhaust is used, and the film is formed by combining heating of the electric heating resistance wire, so that a crystal nucleation energy barrier is effectively increased, and the perovskite thin film with a good mirror surface crystallization effect is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and particularly relates to a vacuum-assisted scraping method for preparing a perovskite thin-film solar cell. Background Art

[0002] Perovskite solar cells are a revolutionary technology in the field of photovoltaics. The composition of perovskite materials usually includes organic cations and inorganic metal halides, which gives perovskite materials excellent photoelectric properties. The structure of perovskite solar cells usually includes an electron transport layer, a perovskite active layer, a hole transport layer and a metal electrode. The working principle of perovskite solar cells is based on the photoelectric effect. When sunlight shines on a perovskite solar cell, the photon energy is absorbed by the perovskite layer and electrons and holes are excited. Electrons jump from the valence band to the conduction band to form free electrons, while holes remain in the valence band to form positive charge centers. These carriers are then collected by the electron transport layer and the hole transport layer, and photocurrent is generated through an external circuit.

[0003] At present, the efficiency of small-area perovskite solar cells has reached 26.7%, which has exceeded the photoelectric conversion efficiency of commercial crystalline silicon solar cells. However, as the area increases, the photoelectric conversion efficiency of large-area perovskite solar cells decays rapidly. The reason is that when preparing large-area perovskite films, the uniformity of the film is difficult to ensure, which may lead to different film quality and thickness in local areas; large-area cells may also produce more losses and dead zones after laser scribing; and the nucleation and crystallization control of large-area perovskite films becomes more difficult. The spin coating process widely used on small-area cells is not applicable to large areas, nor is it suitable for commercial production. Therefore, it is of great significance to improve large-area processes such as coating. Summary of the invention

[0004] The technical problem to be solved by the present invention is how to prepare a large-area perovskite film and improve the uniformity of the film.

[0005] The present invention solves the above technical problems through the following technical means:

[0006] The present invention provides a vacuum-assisted scraping method for preparing a perovskite thin film solar cell. The method for preparing the perovskite thin film layer is as follows:

[0007] The substrate material is fixed on the table of the scraper coating equipment, and the perovskite precursor solution is dripped into the micron-level gap between the substrate material and the scraper to form a liquid curtain. The scraper coating equipment is started, and the perovskite film is scraped by the scraper. At the same time, the vacuum pump is turned on. The vacuum pump is connected to the vacuum knife so that the solvent in the perovskite precursor solution is discharged through the vacuum knife. Combined with the temperature of the electric heating resistance wire, after completing the scraper coating process, the substrate material coated with the perovskite film is placed on a heating table for annealing to obtain a perovskite film layer.

[0008] Beneficial effect: The present invention provides suction by connecting a vacuum pump to a vacuum knife, utilizes the temperature of an electric heating resistor, and combines with conventional scraping equipment to prepare a perovskite film. The saturated vapor pressure on the surface of the perovskite film is reduced by vacuum extraction, and the temperature of the electric heating resistor is utilized to accelerate the volatilization of the solvent in the perovskite precursor, extract the solvent in the perovskite precursor solution, and discharge the solvent from the vacuum knife, thereby assisting the scraping method to prepare a large-area perovskite film. The method of the present invention has a simple preparation process, saves costs to the greatest extent, and realizes green production.

[0009] The present invention replaces the air knife in the original scraping method, uses a vacuum knife with vacuum extraction, and combines electric heating resistance wire heating to assist film formation, effectively increasing the crystal nucleation energy barrier, thereby preparing a perovskite film with good mirror crystallization effect.

[0010] Preferably, the structure of the perovskite thin film solar cell is, from bottom to top: FTO transparent conductive layer, electron transport layer, perovskite thin film layer, hole transport layer, metal electrode, which is a normal structure nip perovskite thin film solar cell; or FTO transparent conductive layer, hole transport layer, perovskite thin film layer, electron transport layer, metal electrode, which is an inverted structure pin perovskite thin film solar cell.

[0011] Preferably, the base material is a transparent conductive glass substrate covered with an electron transport layer, or a transparent conductive glass substrate covered with a hole transport layer.

[0012] Preferably, the vacuum pump has a pumping rate of 250 to 500 L / min; and the temperature of the electric heating resistance wire is 70 to 100°C.

[0013] Preferably, the angle between the vacuum knife and the horizontal operating table is 25-40°.

[0014] Preferably, the vacuum knife is 5 to 10 cm above the horizontal operating table.

[0015] Preferably, the coating equipment table is provided with an electric heat resistance wire, a vacuum knife and a scraper in sequence from left to right, and the distance between the vacuum knife and the scraper is 10 to 15 cm.

[0016] Preferably, the distance between the electric heating resistance wire and the vacuum knife is 3 to 5 cm.

[0017] Preferably, the solvent of the perovskite precursor solution is a mixed solvent of N,N-dimethylformamide, dimethyl sulfoxide and dipropyl sulfoxide, and the mixed volume ratio of N,N-dimethylformamide, dimethyl sulfoxide and dipropyl sulfoxide is 2:1:0.5.

[0018] Beneficial effects: The present invention adopts vacuum exhaust and combines with electric heating resistance wire to replace inert gas such as nitrogen as air knife to extract solvent in perovskite precursor solution, and combines with scraping technology to prepare perovskite film; the present invention uses scraping and vacuum extraction of solvent to be carried out simultaneously, which can better extract the mixed solvent in the perovskite precursor solution, and by introducing dipropyl sulfoxide into the mixed solvent, the film formation is more uniform, and a large-area perovskite film with excellent mirror crystallization effect can be prepared, thereby further obtaining a large-area perovskite thin film battery, and the photoelectric conversion efficiency can reach up to 16.83%. The characteristics of the present invention are simple operation, and it can undertake the existing scraping method wind knife system, providing technical support for the industrialization of large-area perovskite thin film batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the principle of preparing perovskite film by vacuum-assisted doctor blade coating in the embodiment;

[0020] Figure 2 Schematic diagram of the structure of the perovskite thin-film solar cell used in the embodiment, wherein: the left figure is an upright nip structure; the right figure is an inverted pin structure;

[0021] Figure 3 This is the XRD pattern of the perovskite film prepared in Example 1;

[0022] Figure 4 This is a SEM image of the interface of the perovskite film prepared in Example 1;

[0023] Figure 5 This is a SEM image of the surface of the perovskite film prepared in Example 1;

[0024] Figure 6 This is the efficiency diagram of the perovskite thin film solar cell prepared in Example 1;

[0025] Figure 7 This is the efficiency diagram of the perovskite thin film solar cell prepared in Example 2;

[0026] Figure 8 This is the efficiency diagram of the perovskite thin film solar cell prepared in Example 3;

[0027] Fig. 9 This is the efficiency diagram of the perovskite thin film solar cell prepared in Example 4;

[0028] Fig.10 This is the efficiency diagram of the perovskite thin film solar cell prepared in Example 5;

[0029] Fig.11 This is the efficiency diagram of the perovskite thin film solar cell prepared in Example 6;

[0030] Fig.12XRD patterns of perovskite films obtained at different pumping rates for Examples 1, 7 and 8 and Comparative Examples 1-2;

[0031] Fig.13 This is the efficiency diagram of the perovskite thin film solar cell prepared in Comparative Example 3;

[0032] Fig.14 This is the efficiency diagram of the perovskite thin film solar cell prepared in Comparative Example 4;

[0033] Fig.15 This is the SEM image of the surface of the perovskite film prepared in Comparative Example 5. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0036] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0037] Example 1

[0038] This embodiment uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing a perovskite thin-film solar cell. Figure 2 (Left) The structure shown in the figure is used to prepare a formal perovskite thin-film solar cell. The specific preparation process is as follows:

[0039] 1. Place the FTO conductive glass in a beaker of detergent, deionized water, isopropanol, anhydrous ethanol, and deionized water in turn for ultrasonic cleaning for 30 minutes, dry at 60°C, and then place the cleaned FTO conductive glass in a UV-ozone cleaner for 30 minutes to improve the surface contact between the electron transport layer and the substrate to obtain the treated FTO conductive glass.

[0040] 2. Prepare an electron transport layer solution. Take 2.5g of urea and dissolve it in 200mL of deionized water. Then add 2.5mL of 37% hydrochloric acid, 75μL of thioglycolic acid TGA, and 0.548g of SnCl2·2H2O in sequence to prepare a solution. The resulting solution is sealed and placed in a 10°C refrigerator for aging for 15 hours. Then the solution is diluted five times, and the treated FTO conductive glass is immersed in the diluted solution. The reaction is carried out in a 95°C blast oven for 3 hours to obtain an electron transport layer. The reacted FTO conductive glass substrate is then placed in deionized water for ultrasonic cleaning for 5 minutes, and then placed on a 150°C heating plate for annealing for 30 minutes to finally obtain a SnO2 electron transport layer.

[0041] 3. Prepare perovskite precursor solution: 2 mL of N,N-dimethylformamide, 1 mL of dimethyl sulfoxide and 0.5 mL of dipropyl sulfoxide were mixed to obtain a mixed solvent, 0.4879 g of FAI, 1.6384 g of PbI2 and 0.1956 g of CsI were added to the mixed solvent and stirred at room temperature for 2 hours. The mixture was filtered twice with a 0.20 μm PTFE membrane to obtain a 1.5 mol / L perovskite precursor solution.

[0042] 4. Fix the FTO transparent conductive glass substrate with SnO2 electron transport layer prepared on the operating table of the scraper, preheat the electric thermal resistance wire to 70℃, drip 400μL of perovskite precursor solution into the micron-sized gap between the scraper and the substrate to form a liquid curtain, start the scraper coating equipment, and scrape the perovskite film with the scraper. At the same time, turn on the vacuum pump exhaust switch so that the vacuum knife's exhaust rate is 350L / min. The vacuum knife and the horizontal operating table present an angle of 30°. The opening direction of the angle is consistent with the scraping direction. The height of the vacuum knife from the horizontal operating table is 8cm. The electric thermal resistance wire, vacuum knife and scraper are arranged from left to right in sequence. The distance between the vacuum knife and the scraper is 10cm, and the distance between the electric thermal resistance wire and the vacuum knife is 3cm. After completing the scraping process, transfer it to a 150℃ heating table for annealing for 10 minutes. The final area is 225cm 2 Large-area perovskite thin film layer.

[0043] Figure 3 The XRD diagram of the perovskite film of this embodiment shows that characteristic peaks of the crystal plane of α-FAPbI3 appear at about 14° and 28°, indicating that the perovskite film has good crystallinity and the prepared film has high quality. Figure 4-5 This is the SEM image of the interface and surface of the perovskite film of this embodiment. It can be seen from the figure that the prepared perovskite grain size is large and dense, and the grain boundaries are reduced, which greatly inhibits the accumulation of carriers at the grain boundaries, accelerates the transmission of carriers, and reduces the non-radiative recombination of carriers at grain boundaries and defects.

[0044] 5. Prepare Spiro-OMeTAD hole transport layer solution. Add 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN). Stir on a magnetic stirrer at room temperature for 3 hours until dissolved to obtain a lithium salt solution. Add 101 mg of Spiro-OMeTAD, 34 μL of lithium salt solution, and 25.4 μL of TBP solution to 1 ml of chlorobenzene to obtain a Spiro-OMeTAD hole transport layer solution. Add 200 μL of Spiro-OMeTAD solution dropwise into the micron-sized gap formed by the scraper and the substrate to form a liquid curtain. The hole transport layer is prepared by a scraping process.

[0045] 6. Finally, use the thermal evaporation source to A layer of Au with a thickness of 100 nm was evaporated at a speed of 100 nm as a metal top electrode to obtain a perovskite thin film solar cell.

[0046] The perovskite thin film solar cell prepared in this embodiment has an efficiency diagram as shown in FIG. Figure 6 As shown, at 225cm 2 A large-area perovskite thin-film battery achieved an efficiency of 16.83%.

[0047] Example 2

[0048] This embodiment uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing a perovskite thin-film solar cell. Figure 2 (Right) The structure shown in the figure is used to prepare an inverted perovskite thin-film solar cell. The specific preparation process is as follows:

[0049] 1. Place the FTO conductive glass in a beaker of detergent, deionized water, isopropanol, anhydrous ethanol, and deionized water in turn for ultrasonic cleaning for 30 minutes, dry at 60°C, and then place the cleaned FTO conductive glass in a UV-ozone cleaner for 30 minutes to improve the surface contact between the hole transport layer and the substrate to obtain the treated FTO conductive glass.

[0050] 2. Prepare the hole transport layer. Dissolve 0.5 mol of nickel nitrate hexahydrate in 100 mL of deionized water to obtain a dark green solution. Add 10 mol / L of NaOH solution dropwise into the dark green solution until the pH value of the solution is 10. Stir at 40°C for 10 minutes to obtain a colloidal precipitate. Wash the precipitate twice with deionized water and dry it at 80°C for 6 hours to obtain a green powder. Calcinate it at 270°C for 2 hours to obtain a dark black powder NiO x , NiO x The nickel oxide solution was prepared with isopropanol at a ratio of 3 mg:1 mL. 200 μL of the nickel oxide solution was taken and a hole transport layer was prepared by a scraping process.

[0051] 3. Prepare perovskite precursor solution: 2 mL of N,N-dimethylformamide, 1 mL of dimethyl sulfoxide and 0.5 mL of dipropyl sulfoxide were mixed to obtain a mixed solvent, 0.4879 g of FAI, 1.6384 g of PbI2 and 0.1956 g of CsI were added to the mixed solvent and stirred at room temperature for 2 hours. The mixture was filtered twice with a 0.20 μm PTFE membrane to obtain a 1.5 mol / L perovskite precursor solution.

[0052] 4. Fix the FTO transparent conductive glass substrate with prepared hole transport layer on the operating table of the scraper, preheat the electric thermal resistance wire to 70℃, drip 400μL perovskite solution into the micron-sized gap between the scraper and the substrate to form a liquid curtain, start the scraper coating equipment, and scrape the perovskite film with the scraper. At the same time, turn on the vacuum pump exhaust switch to make the vacuum knife exhaust rate of 350L / min. The vacuum knife and the horizontal operating table present an angle of 30°. The opening direction of the angle is consistent with the scraping direction. The height of the vacuum knife from the horizontal operating table is 8cm. The electric thermal resistance wire, vacuum knife and scraper are arranged from left to right in sequence. The distance between the vacuum knife and the scraper is 10cm, and the distance between the electric thermal resistance wire and the vacuum knife is 4cm. After completing the scraping process, transfer it to a 150℃ heating table for annealing for 10 minutes. The final area is 225cm 2 Large-area perovskite thin film layer.

[0053] 5. Prepare the electron transport layer using thermal evaporation technology. Steaming and growing a layer of C 60 and BCP as electron transport layer, C 60 The thickness is 20nm and the BCP thickness is 7nm.

[0054] 6. Finally, use the thermal evaporation source to A layer of Ag with a thickness of 100 nm was evaporated at a speed of 100 nm as a metal electrode to obtain a perovskite thin film solar cell.

[0055] The perovskite thin film solar cell prepared in this embodiment has an efficiency diagram as shown in FIG. Figure 7 As shown, at 225cm 2 An efficiency of 14.73% was obtained on large-area perovskite thin-film batteries.

[0056] Example 3

[0057] This embodiment uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing a perovskite thin-film solar cell. Figure 2 (Left) The structure shown in the figure is used to prepare a formal perovskite thin-film solar cell. The specific preparation process is as follows:

[0058] 1. Place the FTO conductive glass in a beaker of detergent, deionized water, isopropanol, anhydrous ethanol, and deionized water in turn for ultrasonic cleaning for 30 minutes, dry at 60°C, and then place the cleaned FTO conductive glass in a UV-ozone cleaner for 30 minutes to improve the surface contact between the electron transport layer and the substrate to obtain the treated FTO conductive glass.

[0059] 2. Prepare the electron transport layer solution, dissolve 2.5g of urea in 200mL of deionized water, then add 75μL of thioglycolic acid TGA and 0.4g of 99% pure stannous sulfate SnSO4 in sequence, keep it in a refrigerator at low temperature overnight, and naturally age it under ambient conditions for 20 minutes before use. Then dilute the solution five times, immerse the treated FTO conductive glass in the solution, and deposit the electron transport layer by chemical water bath CBD method. React in a 95℃ blast oven for 3 hours to obtain the electron transport layer. Place the reacted FTO conductive glass substrate in deionized water for ultrasonic cleaning for 5 minutes, and then place it on a 150℃ heating plate for annealing for 30 minutes to finally obtain the SnO2 electron transport layer.

[0060] 3. Prepare perovskite precursor solution: 2 mL of N,N-dimethylformamide, 1 mL of dimethyl sulfoxide and 0.5 mL of dipropyl sulfoxide were mixed to obtain a mixed solvent, 0.4879 g of FAI, 1.6384 g of PbI2 and 0.1956 g of CsI were added to the mixed solvent and stirred at room temperature for 2 hours. The mixture was filtered twice with a 0.20 μm PTFE membrane to obtain a 1.5 mol / L perovskite precursor solution.

[0061] 4. Fix the FTO transparent conductive glass substrate with SnO2 electron transport layer prepared on the operating table of the scraper, preheat the electric thermal resistance wire to 70℃, drip 500μL of perovskite precursor solution into the micron-sized gap between the scraper and the substrate to form a liquid curtain, start the scraper coating equipment, and scrape the perovskite film with the scraper. At the same time, turn on the vacuum pump exhaust switch so that the vacuum knife's exhaust rate is 450L / min. The vacuum knife and the horizontal operating table present an angle of 30°. The opening direction of the angle is consistent with the scraping direction. The height of the vacuum knife from the horizontal operating table is 5cm. The electric thermal resistance wire, vacuum knife and scraper are arranged from left to right in sequence. The distance between the vacuum knife and the scraper is 12cm, and the distance between the electric thermal resistance wire and the vacuum knife is 4cm. After completing the scraping process, transfer it to a 150℃ heating table for annealing for 10 minutes. The final area is 225cm 2 Large-area perovskite thin film layer.

[0062] 5. Based on the previous step, a layer of NiO is grown using the ALD atomic layer deposition process x The hole transport layer had a thickness of 10 nm.

[0063] 6. Finally, thermal evaporation technology is used to A layer of Au with a thickness of 100 nm was evaporated at a speed of 100 nm as the top electrode to obtain a perovskite thin film solar cell.

[0064] The perovskite thin film solar cell prepared in this embodiment has an efficiency diagram as shown in FIG. Figure 8 As shown, at 225cm 2 An efficiency of 16.71% was obtained on large-area perovskite thin-film batteries.

[0065] Example 4

[0066] This embodiment uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing a perovskite thin-film solar cell. Figure 2 (Right) The structure shown in the figure is used to prepare an inverted perovskite thin-film solar cell. The specific preparation process is as follows:

[0067] 1. Place the FTO conductive glass in a beaker of detergent, deionized water, isopropanol, anhydrous ethanol, and deionized water in turn for ultrasonic cleaning for 30 minutes, dry at 60°C, and then place the cleaned FTO conductive glass in a UV-ozone cleaner for 30 minutes to improve the surface contact of the substrate to obtain the treated FTO conductive glass.

[0068] 2. Prepare the hole transport layer. Dissolve 0.5 mol of nickel nitrate hexahydrate in 100 mL of deionized water to obtain a dark green solution. Add 10 mol / L of NaOH solution dropwise into the dark green solution until the pH value of the solution is 10. Stir at 40°C for 10 minutes to obtain a colloidal precipitate. Wash the precipitate twice with deionized water and dry at 80°C for 6 hours to obtain a green powder. Calcinate at 270°C for 2 hours to obtain a dark black powder NiO x, NiO x The nickel oxide solution was prepared with isopropanol at a ratio of 3 mg:1 mL. 200 μL of the nickel oxide solution was taken and a hole transport layer was prepared by a scraping process.

[0069] 3. Prepare perovskite precursor solution: 2 mL of N,N-dimethylformamide, 1 mL of dimethyl sulfoxide and 0.5 mL of dipropyl sulfoxide were mixed to obtain a mixed solvent, 0.6505 g of FAI, 2.1845 g of PbI2 and 0.2608 g of CsI were added to the mixed solvent and stirred at room temperature for 2 hours. The mixture was filtered twice with a 0.22 μm PTFE membrane to obtain a 2 mol / L perovskite precursor solution.

[0070] 4. Fix the FTO transparent conductive glass substrate with prepared hole transport layer on the operating table of the scraper, preheat the electric thermal resistance wire to 80℃, drip 500μL of perovskite precursor solution into the micron-sized gap between the scraper and the substrate to form a liquid curtain, start the scraper coating equipment, and scrape the perovskite film with the scraper. At the same time, turn on the vacuum pump exhaust switch so that the vacuum knife's exhaust rate is 450L / min. The vacuum knife and the horizontal operating table present a 30° angle. The opening direction of the angle is consistent with the scraping direction. The vacuum knife is 5cm high from the horizontal operating table. The electric thermal resistance wire, vacuum knife and scraper are arranged from left to right in sequence. The distance between the vacuum knife and the scraper is 12cm, and the distance between the electric thermal resistance wire and the vacuum knife is 5cm. After completing the scraping process, transfer it to a 150℃ heating table for annealing for 10 minutes. The final area is 225cm 2 Large-area perovskite thin film layer.

[0071] 5. Prepare the electron transport layer using thermal evaporation technology. Steaming and growing a layer of C 60 and BCP as electron transport layer, C 60 The thickness is 20nm and the BCP thickness is 7nm.

[0072] 6. Finally, use the thermal evaporation source to A layer of Ag with a thickness of 100 nm was evaporated at a speed of 100 nm as a metal electrode to obtain a perovskite thin film solar cell.

[0073] The perovskite thin film solar cell prepared in this embodiment has an efficiency diagram as shown in FIG. Fig. 9 As shown, at 225cm 2 An efficiency of 12.69% was obtained on large-area perovskite thin-film batteries.

[0074] Example 5

[0075] This embodiment uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing a perovskite thin-film solar cell. Figure 2 (Left) The structure shown in the figure is used to prepare a formal perovskite thin-film solar cell. The specific preparation process is as follows:

[0076] 1. Place the FTO conductive glass in a beaker of detergent, deionized water, isopropanol, anhydrous ethanol, and deionized water in turn for ultrasonic cleaning for 30 minutes, dry at 60°C, and then place the cleaned FTO conductive glass in a UV-ozone cleaner for 30 minutes to improve the surface contact between the electron transport layer and the substrate to obtain the treated FTO conductive glass.

[0077] 2. Prepare the electron transport layer solution, dissolve 2.5g of urea in 200mL of deionized water, then add 75μL of thioglycolic acid TGA and 0.4g of 99% pure stannous sulfate SnSO4 in sequence, keep it in a refrigerator at low temperature overnight, and naturally age it under ambient conditions for 20 minutes before use. Then dilute the solution five times, immerse the treated FTO conductive glass in the solution, and deposit the electron transport layer by chemical water bath CBD method. React in a 95℃ blast oven for 3 hours to obtain the electron transport layer. Place the reacted FTO conductive glass substrate in deionized water for ultrasonic cleaning for 5 minutes, and then place it on a 150℃ heating plate for annealing for 30 minutes to finally obtain the SnO2 electron transport layer.

[0078] 3. Prepare perovskite precursor solution: 2 mL of N,N-dimethylformamide, 1 mL of dimethyl sulfoxide and 0.5 mL of dipropyl sulfoxide are mixed to obtain a mixed solvent, 124 mg of PbCl2 and 23 mg of CH3NH3I are reacted in the mixed solvent to generate a CH3NH3PbI3 solution; 92 mg of PbBr2 and 23 mg of CH3NH3Br are reacted in a mixed solvent to generate a CH3NH3PbBr3 solution, and then the CH3NH3PbI3 and CH3NH3PbBr3 solutions are mixed in a ratio of 3:2 to obtain CH3NH3Pb(I 0.6 Br 0.4 )3 Perovskite precursor solution, the perovskite precursor solution was stirred at room temperature for 2 hours, and filtered twice using a 0.20 μm PTFE membrane before use.

[0079] 4. Fix the FTO transparent conductive glass substrate with SnO2 electron transport layer prepared on the operating table of the scraper, preheat the electric thermal resistance wire to 70℃, drip 560μL of perovskite precursor solution into the micron-sized gap between the scraper and the substrate to form a liquid curtain, start the scraper coating equipment, and scrape the perovskite film with the scraper. At the same time, turn on the vacuum pump exhaust switch to make the vacuum knife exhaust rate 450L / min. The vacuum knife and the horizontal operating table present an angle of 35°. The opening direction of the angle is consistent with the scraping direction. The height of the vacuum knife from the horizontal operating table is 5cm. The electric thermal resistance wire, vacuum knife and scraper are arranged from left to right in sequence. The distance between the vacuum knife and the scraper is 12cm, and the distance between the electric thermal resistance wire and the vacuum knife is 4cm. After completing the scraping process, transfer it to a 150℃ heating table for annealing for 10 minutes. The final area is 225cm 2 Large-area perovskite thin film layer.

[0080] 5. Prepare Spiro-OMeTAD hole transport layer solution. Add 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN). Stir on a magnetic stirrer at room temperature for 3 hours until dissolved to obtain a lithium salt solution. Take 101 mg of Spiro-OMeTAD, 34 μL of lithium salt solution, and 25.4 μL of TBP solution and add them to 1 ml of chlorobenzene to obtain a Spiro-OMeTAD hole transport layer solution. Add 200 μL of Spiro-OMeTAD solution dropwise into the micron-sized gap formed by the scraper and the substrate to form a liquid curtain. The hole transport layer is prepared by a scraping process.

[0081] 6. Finally, thermal evaporation technology is used to A layer of Au with a thickness of 100 nm was evaporated at a speed of 100 nm as the top electrode to obtain a perovskite thin film solar cell.

[0082] The perovskite thin film solar cell prepared in this embodiment has an efficiency diagram as shown in FIG. Fig.10 As shown, at 225cm 2 A large-area perovskite thin-film battery achieved an efficiency of 16.68%.

[0083] Example 6

[0084] This embodiment uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing a perovskite thin-film solar cell. Figure 2 (Right) The structure shown in the figure is used to prepare an inverted perovskite thin-film solar cell. The specific preparation process is as follows:

[0085] 1. Place the FTO conductive glass in a beaker of detergent, deionized water, isopropanol, anhydrous ethanol, and deionized water in turn for ultrasonic cleaning for 30 minutes, dry at 60°C, and then place the cleaned FTO conductive glass in a UV-ozone cleaner for 30 minutes to improve the surface contact between the hole transport layer and the substrate to obtain the treated FTO conductive glass.

[0086] 2. Prepare a hole transport layer, use poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] PTAA as the hole transport layer, take 631 mg of PTAA and dissolve it in 2 mL of chlorobenzene, take 200 μL of the solution, and use the scraping method to prepare a hole transport layer on the FTO conductive glass. After scraping, anneal the FTO conductive glass at 120 ° C for 10 minutes to prepare a 20 nm hole transport layer.

[0087] 3. Prepare perovskite precursor solution: 2 mL of N,N-dimethylformamide, 1 mL of dimethyl sulfoxide and 0.5 mL of dipropyl sulfoxide are mixed to obtain a mixed solvent, 124 mg of PbCl2 and 23 mg of CH3NH3I are reacted in the mixed solvent to generate a CH3NH3PbI3 solution; 92 mg of PbBr2 and 23 mg of CH3NH3Br are reacted in a mixed solvent to generate a CH3NH3PbBr3 solution, and then the CH3NH3PbI3 and CH3NH3PbBr3 solutions are mixed in a ratio of 3:2 to obtain CH3NH3Pb(I 0.6 Br 0.4 )3 Perovskite precursor solution, the perovskite precursor solution was stirred at room temperature for 2 hours, and filtered twice using a 0.20 μm PTFE membrane before use.

[0088] 4. Fix the FTO transparent conductive glass substrate with the prepared hole transport layer on the operating table of the scraper, preheat the electric thermal resistance wire to 70°C, and drip 560μL of perovskite precursor solution into the micron-sized gap between the scraper and the substrate to form a liquid curtain to start the scraper. Scrape the perovskite film with the scraper. At the same time, turn on the vacuum pump's exhaust switch to make the vacuum knife's exhaust rate 450L / min. The vacuum knife and the horizontal operating table present a 35° angle. The opening direction of the angle is consistent with the scraping direction. The vacuum knife is 5cm high from the horizontal operating table. The electric thermal resistance wire, vacuum knife and scraper are arranged from left to right in sequence. The distance between the vacuum knife and the scraper is 12cm, and the distance between the electric thermal resistance wire and the vacuum knife is 4cm. After completing the scraping process, transfer it to a 150°C heating table for annealing for 10 minutes, and finally obtain an area of ​​225cm 2 Large-area perovskite thin film layer.

[0089] 5. Prepare the electron transport layer using thermal evaporation technology. Steaming and growing a layer of C 60 and BCP as electron transport layer, C 60 The thickness is 20nm and the BCP thickness is 7nm.

[0090] 6. Finally, use the thermal evaporation source to A layer of Ag with a thickness of 100 nm was evaporated at a speed of 100 nm as a metal electrode to obtain a perovskite thin film solar cell.

[0091] The perovskite thin film solar cell prepared in this embodiment has an efficiency diagram as shown in FIG. Fig.11 As shown, at 225cm 2 An efficiency of 14.83% was obtained on large-area perovskite thin-film batteries.

[0092] Example 7

[0093] This embodiment uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing a perovskite thin-film solar cell. Figure 2 (Left picture) The structure shown is used to prepare a formal perovskite thin-film solar cell. The difference between this embodiment and embodiment 1 is that the vacuum knife's exhaust rate is 450 L / min.

[0094] Example 8

[0095] This embodiment uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing a perovskite thin-film solar cell. Figure 2 (Left picture) The structure shown is used to prepare a formal perovskite thin-film solar cell. The difference between this embodiment and embodiment 1 is that the vacuum knife's exhaust rate is 250L / min.

[0096] Comparative Example 1

[0097] This comparative example uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing perovskite thin-film solar cells. Figure 2 (Left picture) The structure shown is used to prepare a formal perovskite thin film solar cell. The difference between this comparative example and Example 1 is that the vacuum knife's exhaust rate is 150 L / min.

[0098] Comparative Example 2

[0099] This comparative example uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing perovskite thin-film solar cells. Figure 2 (Left picture) The structure shown is used to prepare a formal perovskite thin film solar cell. The difference between this comparative example and Example 1 is that the vacuum knife's exhaust rate is 100 L / min.

[0100] from Fig.12 It can be seen that when the vacuum knife pumping rate is below 250L / min, the prepared perovskite film does not have characteristic peaks belonging to the crystal plane of α-FAPbI3 at 14° and 28°, indicating that the α-phase-FAPbI3 perovskite film is not completely generated. When the vacuum knife pumping rate is 250L / min, characteristic peaks belonging to the crystal plane of α-FAPbI3 appear around 14° and 28°, and with the increase of the vacuum knife pumping rate, the perovskite film has a stronger diffraction peak intensity, indicating that the perovskite film has better crystallinity and the prepared film quality is higher.

[0101] Comparative Example 3

[0102] This comparative example uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing perovskite thin-film solar cells. Figure 2 (Left picture) The structure shown is used to prepare a formal perovskite thin film solar cell. The difference between this comparative example and Example 1 is that the height of the vacuum knife from the horizontal operating table is 13 cm.

[0103] The titanium ore thin film solar cell prepared in this comparative example has an efficiency diagram as shown in FIG. Fig.13 As shown, at 225m 2 The efficiency of the large-area perovskite thin film battery is only 11.68%. When the vacuum knife is too high from the horizontal operating table, the crystallization quality of the perovskite film is affected, thereby affecting the photoelectric conversion efficiency of the final perovskite thin film solar cell.

[0104] Comparative Example 4

[0105] This comparative example uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing perovskite thin-film solar cells. Figure 2 (Left picture) The structure shown is used to prepare a formal perovskite thin film solar cell. The difference between this comparative example and Example 1 is that the distance between the vacuum knife and the scraper is 5 cm.

[0106] The titanium ore thin film solar cell prepared in this comparative example has an efficiency diagram as shown in FIG. Fig.14 As shown, at 225cm 2 The efficiency of large-area perovskite thin-film solar cells is only 10.87%. When the distance between the vacuum knife and the scraper is too close, the suction of the vacuum knife will affect the stability of the scraping, thereby affecting the quality of the final scraped perovskite film, and ultimately affecting the photoelectric conversion efficiency of the perovskite thin-film solar cell.

[0107] Comparative Example 5

[0108] This comparative example uses FTO transparent conductive glass (15cm×15cm) as a substrate to provide a vacuum-assisted scraping method for preparing perovskite thin-film solar cells. Figure 2 (Left Figure) shows the structure of the preparation of a formal perovskite thin film solar cell. The difference between this comparative example and Example 1 is that the mixed solvent of the perovskite precursor solution is different. The mixed solvent is a mixed solvent obtained by mixing 2mL of N,N-dimethylformamide, 1mL of dimethyl sulfoxide and 1mL of dipropyl sulfoxide. The surface SEM image of the perovskite film prepared in this comparative example is as follows Fig.15 As shown in Figure 2, as the proportion of dipropyl sulfoxide in the mixed solvent increases, the nucleation energy barrier increases, affecting the crystal nucleation and making the nucleation difficult. Fig.15It can be seen that the prepared perovskite film has poor surface morphology, uneven crystal size, and increased surface defects, which leads to poor quality of the perovskite film and seriously affects the photoelectric performance of the final perovskite thin film solar cell.

[0109] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A vacuum-assisted doctor blade coating method for preparing a perovskite thin film solar cell, characterized in that: The method for preparing the perovskite thin film layer is specifically as follows: The substrate material is fixed on the table of the scraper coating equipment, and the perovskite precursor solution is dripped into the micron-level gap between the substrate material and the scraper to form a liquid curtain. The scraper coating equipment is started, and the perovskite film is scraped by the scraper. At the same time, the vacuum pump is turned on. The vacuum pump is connected to the vacuum knife so that the solvent in the perovskite precursor solution is discharged through the vacuum knife. Combined with the temperature of the electric heating resistance wire, after completing the scraper coating process, the substrate material coated with the perovskite film is placed on a heating table for annealing to obtain a perovskite film layer.

2. The method for preparing a perovskite thin film solar cell by vacuum assisted doctor blade coating according to claim 1, characterized in that: The structure of the perovskite thin film solar cell is, from bottom to top: FTO transparent conductive layer, electron transport layer, perovskite thin film layer, hole transport layer, metal electrode, which is a normal structure nip perovskite thin film solar cell; or FTO transparent conductive layer, hole transport layer, perovskite thin film layer, electron transport layer, metal electrode, which is an inverted structure pin perovskite thin film solar cell.

3. The method for preparing a perovskite thin film solar cell by vacuum assisted doctor blade coating according to claim 2, characterized in that: The base material is a transparent conductive glass substrate covered with an electron transport layer, or a transparent conductive glass substrate covered with a hole transport layer.

4. The method for preparing a perovskite thin film solar cell by vacuum assisted doctor blade coating according to claim 1, characterized in that: The vacuum knife has an air extraction rate of 250 to 500 L / min; the temperature of the electric heating resistance wire is 70 to 100°C.

5. The method for preparing a perovskite thin film solar cell by vacuum assisted doctor blade coating according to claim 1, characterized in that: The angle between the vacuum knife and the horizontal operating table is 25-40 degrees.

6. The method for preparing a perovskite thin film solar cell by vacuum assisted doctor blade coating according to claim 5, characterized in that: The height of the vacuum knife from the horizontal operating table is 5 to 10 cm.

7. The method for preparing a perovskite thin film solar cell by vacuum assisted doctor blade coating according to claim 6, characterized in that: The table of the scraping equipment is provided with an electric heat resistance wire, a vacuum knife and a scraper in sequence from left to right, and the distance between the vacuum knife and the scraper is 10 to 15 cm.

8. The method for preparing a perovskite thin film solar cell by vacuum assisted doctor blade coating according to claim 7, characterized in that: The distance between the electric heating resistance wire and the vacuum knife is 3 to 5 cm.

9. The method for preparing a perovskite thin film solar cell by vacuum assisted doctor blade coating according to any one of claims 1 to 5, characterized in that: The solvent of the perovskite precursor solution is a mixed solvent of N,N-dimethylformamide, dimethyl sulfoxide and dipropyl sulfoxide, and the volume ratio of the N,N-dimethylformamide, dimethyl sulfoxide and dipropyl sulfoxide is 2:1:0.5.